Limitation towards anti-vaccine group: does it violate fundamental right? - Masyitah Ayoib,; Siti Aishah Norizan,; Nabeel Althabhawi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Covid-19 vaccination program was introduced by the Malaysian government to accelerate the rate of herd immunity within a short amount of time to protect the people from the Covid-19 virus. Despite the free immunization program and the proven ability to reduce the side effects of the virus, there are still people who refused to receive the vaccination programme for non-medical reasons. The recent restrictions imposed on the people who refused to receive the COVID-19 vaccine sparked the debate of whether it deprives the people of their fundamental rights under the Federal Constitution. Therefore, a question arises of whether the decision made by the government is morally or legally right. This article will cover the complete range of debates between legal positivists, who want to maintain a conceptual divide between law and morality, and those, such as natural theorists, who reject the idea of a law/moral separation on the matter concerning vaccination refusal and the restrictions imposed on them. Our findings indicate that the restrictions on vaccination refusal do not comply with the theories propounded by naturalists. However, the restrictions are in alignment with the legal positivists as it regards law and morality as within different ambits. So, the restrictions that come with the vaccination refusal do deprive the citizens of their fundamental rights but are in accordance with the Federal Constitution.